The Effect of Cognitive Apprenticeship Style and Keller Plan on Learning Volleyball Underarm Serving In First Year secondary School Students - Salman, Wissam; Moayad, Ghada (Journal of Physical Education, 2020)
The research aim at identifying the effect of cognitive apprenticeship and Keller plan on learning underarm serving in volleyball for 1st-grade secondary school students. The researchers hypothesized statistical differences between pre and posttests in all three groups in learning volleyball serving as well as statistical differences in posttests. The researchers used the experimental method on three groups; two experimental and one controlling group on (112) first-grade secondary school students (Mohammed Baqer Al Sedar). The cognitive apprenticeship was used in the first experimental group, Keller plan on the second group and the command style on the controlling group. The data was collected and treated using proper statistical operations to conclude that the cognitive apprenticeship and keller plan have a great effect on learning serving in volleyball compared to the style followed by the teacher.